Development of 3D printing technology for the manufacture of flexible electric double-layer capacitors. Issue 8 (11th June 2018) - Areir, Milad; Xu, Yanmeng; Harrison, David; Fyson, John; Zhang, Ruirong
ABSTRACT: This study presents a novel process and manufacturing system for the fabrication of Electric Double-Layer Capacitors (EDLCs) as energy storage devices. It shows an approach for printing multilayer EDLC components using 3D printing technology. This process allows layers of activated carbon (AC) slurry, gel electrolyte, and composite solid filaments to be printed with high precision. The study describes the detailed process of deposition of the AC and gel electrolyte using the dual nozzle system. The performance of the flexible EDLCs manufactured by 3D printing in a rectilinear infill pattern has been investigated. It describes the energy storage performance of the printed supercapacitors in relation to the differences in thickness of the AC printed layers and the differences in density of gel electrolyte. A supercapacitor based on printed AC and composite materials displays a specific capacitance of 38.5 mF g −1 when measured at a potential rate change of 20 mV s −1 and a current density of 0.136 A g −1 . The highest energy density value for the flexible EDLC was 0.019 Wh kg −1 and power density of 165.0 W kg −1 in 1.6 M H2 SO4 /PVA gel electrolyte.